(untitled) (International relations and international law Journal, 2016)
In the article "Transnational corporations in the telecommunications marketof Kazakhstan"examines the mostbasic problems ofeconomic and political integrationin the era ofglobalization and thetelecommunicationsindustry, which is part ofthe world modern economy.Expansion oftelecommunications infrastructure, the implementation of new ideas, new technologies in the industryTelecommunicationshas a positive impacton thepolitical and social lifeof the Republic of Kazakhstan.The articlealsoreviews the achievementsof large multinationalsoperatingin the information marketand analyzedas a major factorliftingthe national economy,the growth ofbusiness and intellectualactivity, and raisesthe country’s prestigein the international community.Advanced development oftelecommunicationsis a prerequisite forthe creation ofbusiness infrastructure, the creation of favorableconditions for attractinginvestments into the country, the development of moderninformation technology.